1993
DOI: 10.1159/000139097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vasoactive Intestinal Peptide and Naloxone Combination on Urinary N-Acetyl-&beta;-<i>D</i>-Glucosaminidase Level and Kidney Histology of Rats Exposed to Severe Hemorrhage

Abstract: Renal hypoperfusion which occurs in hemorrhagic shock creates an environment in which cellular injury and organ dysfunction can occur during the episode of shock as well as re-oxygenation and reperfusion. At the same time, mast cell degranulation which is observed during hemorrhage may have an additinal deleterious effect on the kidney. Twenty-two (Mus norvegicus albinos) rats (200–250 g) of either sex were used. The animals were divided into three groups. Group 1, the control group, was exposed to a 40% hemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…In our previous reports, it was stated that VIP administration in experimental hemorrhagic shock models inhibits mast cell degranulation, increases the survival rate, and protects the renal tissue from reperfusion injury. 19,20,24 In our subsequent studies, it was also shown that VIP protects the renal, retinal, and skeletal muscle tissue from ischemia reperfusion injury by acting as an antioxidant. 25‐27 In addition to experimental hemorrhagic shock model, VIP also inhibits mast cell degranulation and proliferation and decreases histamine level in testicular tissue of rats exposed to cold‐restraint stress.…”
mentioning
confidence: 87%
“…In our previous reports, it was stated that VIP administration in experimental hemorrhagic shock models inhibits mast cell degranulation, increases the survival rate, and protects the renal tissue from reperfusion injury. 19,20,24 In our subsequent studies, it was also shown that VIP protects the renal, retinal, and skeletal muscle tissue from ischemia reperfusion injury by acting as an antioxidant. 25‐27 In addition to experimental hemorrhagic shock model, VIP also inhibits mast cell degranulation and proliferation and decreases histamine level in testicular tissue of rats exposed to cold‐restraint stress.…”
mentioning
confidence: 87%
“…In the kidney, naloxone at high concentrations has been shown to reduce damage during ischemia [3], hemorrhagic shock [4, 5]and chronic renal failure [6]. Also in specific conditions naloxone, at high doses, has been implicated in alteration of renal salt and water excretion [7, 8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…In the spinal cord, chronic morphine produced increased binding sites for the 6 agonist [D-Ala2]deltorphin-I but not for the ~ ligand FK33,824, so that the 6 receptors may be of special relevance with regard to the development of tolerance in the spinal cord (189). Although chronic morphine produced no change in dynorphin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) immunoreactivity in the brain, removal of the morphine rats reduced dynorphin(l-17) in the nucleus accumbens, suggesting a possible suppressive role of the dynorphinergic neurons in the limbic system during dependence (560), although its nature was unclear.…”
Section: Tolerance and Dependencementioning
confidence: 99%
“…When Met-enkephalin was injected into the medial hyperstriatum, it produced amnesia, but when administered to the lobus parolfactorius, it had no effect on chicks trained on a peck-avoidance task (91). In the same situation, microinjection of DAMGO into the medial hyperstriatum also failed to alter retention (301), but injection ofdynorphin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) into that area did impair memory, (92), suggesting that in this structure of the brain, the effect was receptor specific. In these studies, the opiates were given before training, which could have affected the results, as found in a comparison of pre-and posttraining injections of TAPA.…”
Section: Learning Memory and Rewardmentioning
confidence: 99%
See 1 more Smart Citation